Conference on Research Done by School Students and Teachers (2011)
The Conference on Research Conducted by School Teachers and Students is the product of the interest of a group of institutions in fostering scientific spirit in children and teachers in the city. It highlights the importance of the role that teachers play in the process of bringing children closer to science.